Body fat in children and adolescents participating in organized sports: Descriptive epidemiological study of 6048 Latvian athletes. Issue 6 (August 2015) - Kalnina, Liga; Sauka, Melita; Timpka, Toomas; Dahlström, Örjan; Nylander, Eva; Selga, Guntars; Ligere, Renate; Karklina, Helena; Priedite, Ilga S.; Larins, Viesturs
Background: Pressure among young athletes to meet body composition goals may lead to poor nutrition and affect growth. Aims: To examine the proportion of body fat (%BF), measured by bioimpedance analysis, among Latvian children and adolescents participating in organized sports. Methods: Our study had a nationally representative sample of 6048 young athletes, aged 10–17 years. Their %BF was measured using a multifrequency, 8-pole, bioelectrical impedance leg-to-hand analyzer. Results: About 19.2% (CI 14.4–20.0) of boys and 15.1% (CI 14.0–16.3) of girls had a %BF value below the recommended levels. The %BF in young female athletes participating in aesthetic sports was lower than among their peers participating in other sports. Young male athletes participating in aesthetic sports had lower %BF levels at 10 and 12 years of age, compared with participants in weight-class sports; and lower levels of %BF from age 10–14 years, compared with participants in non-weight-sensitive sports. Conclusions: Almost every fifth child and adolescent participating in organized sports displayed critically low body fat levels. Body fat needs to be assessed regularly in young athletes, to prevent negative consequences on health.